The amount of humeral head impaction of proximal humeral fractures fixed with the Humerusblock device - Carbone, Stefano (Springer Berlin Heidelberg, 2014)
PURPOSE: The Humerusblock is a minimally invasive device allowing fixation of proximal humeral fractures. A drawback of the device is possible K-wire perforation of the head with the need for early removal of the implant. We assessed the amount of humeral head impaction and its role in the postoperative varus/valgus deviation of the humeral head in fractures of the upper humerus treated with Humerusblock. METHODS: Fractures were classified according to the Codman-Lego system. The length of the posteromedial metaphyseal extension and integrity of medial hinge were measured; metaphyseal comminution was assessed. Accuracy of fracture reduction was classified as excellent to poor. An original method of measurement of amount of postoperative impaction of the humeral head was developed. The impaction and varus/valgus inclination of the heads were measured comparing postoperative and three-month follow-up radiographs. Constant score and its relation to sintering was calculated at 12-month follow-up. RESULTS: Forty-three fractures were available for follow-up. The amount of humeral head impaction was 3.9 mm on average and was directly correlated with patient’s age, sex, Codman-Lego classification, varus inclination and mataphyseal comminution. The postoperative cervico-diaphyseal angle was restored in 35 cases, with 81 % good results. The Humerusblock was removed in 41 % of cases because of K-wire perforation of the humeral head. A negative correlation was found between impaction and Constant score. CONCLUSIONS: The amount of humeral head impaction is related to patients’ age, sex, and fracture patterns, being the most prone to compaction those with metaphyseal comminution. Humeral head impaction negatively affects final Constant score. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00264-014-2327-9) contains supplementary material, which is available to authorized users.